Preparation method of high-specific-capacitance supercapacitor electrode based on carbon material
By mixing the carbon material with sodium alginate or carboxymethyl cellulose aqueous solution and crosslinking and electrochemical treatment, a high specific capacitance supercapacitor electrode was prepared, which solved the problem of improving the performance of the carbon material electrode, and achieved widening the electrochemical stability window and significant improvement of the specific capacitance.
Patent Information
- Application Number
- CN202411845042.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing carbon material supercapacitor has a small electrochemical stability window in acidic and alkaline aqueous electrolytes, resulting in a lower specific capacitance, making it difficult to increase the energy density without damaging performance.
High specific capacitance supercapacitor electrodes were prepared by mixing the carbon material with sodium alginate or aqueous carboxymethyl cellulose to form a slurry and coated on the substrate to form a film, followed by crosslinking and electrochemical treatment.
The electrochemical stability window of carbon materials has been widened to 1.3V, the specific capacitance has been increased to 395F/g, and the capacitance performance of 99% is maintained under high cycle times, solving the problem of improving the performance of carbon materials electrodes in the prior art.
Smart Images

Figure CN119650321A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of supercapacitors, and in particular relates to a method for preparing a high specific capacitance supercapacitor electrode based on carbon materials. Background Art
[0002] Supercapacitors are particularly suitable for applications that require frequent, short-term energy storage and release due to their high power density and long cycle life, and have received widespread attention. However, their low energy density (about one-tenth of lead-acid batteries) severely limits their wider application. The relationship between the energy density (E) of a supercapacitor and its capacitance (C) and operating voltage (U) is E = CU 2 / 2. Therefore, E can be increased by expanding U and enhancing C, which are determined by the electrochemical stable potential window and specific capacitance of the electrode respectively.
[0003] Carbon materials (such as porous activated carbon, graphene, and carbon nanotubes) are considered to be the most attractive supercapacitor electrode materials because of their light weight, high ion accessible specific surface area, high electronic conductivity, high electrochemical stability, and fast ion transfer kinetics. Currently, commercial supercapacitor devices are basically constructed with activated carbon as the active material. However, the electrochemical stability window of carbon materials in acidic and alkaline aqueous electrolytes with high ionic conductivity, small ion size, and high safety is mostly ≤1.0V, and they mainly rely on the double electric layer (EDLC) mechanism for energy storage, resulting in a low specific capacitance (mostly <300F / g). This severely limits the improvement of the energy density of widely used carbon-based supercapacitors.
[0004] In order to improve the electrochemical stability window of carbon materials, previous studies have mainly focused on changing the composition of electrolytes, such as salt-in-water electrolytes, organic electrolytes, and ionic liquid electrolytes. However, these electrolytes have significant disadvantages of large ion size and low conductivity, and also bring about problems such as cost and safety. Assembling carbon materials into electrodes often requires the use of binders to bond them as a whole to ensure the mechanical stability and electronic path of the electrode. However, commonly used binders are ion insulating (such as polyvinylidene fluoride), which makes the active area blocked by the binder unable to participate in energy storage and become a "dead capacitor", and the capacitance of the carbon material is difficult to fully exert. In order to further improve the capacitance of carbon materials, pseudocapacitance can be introduced into them. Previous researchers mainly achieved this by doping nitrogen in carbon materials or compounding them with pseudocapacitive materials. However, these practices often involve complex synthesis steps and will lead to problems of poor cycle stability and rate performance.
[0005] At present, research on expanding the electrochemical stability window of carbon materials, enhancing their capacitance, and retaining high rate performance and high cycle stability is still blank. Solving this problem has important theoretical and practical significance. Summary of the invention
[0006] In order to overcome the above-mentioned shortcomings of the prior art, the present invention proposes a method for preparing a high specific capacitance supercapacitor electrode based on carbon materials.
[0007] In one aspect, the present invention provides a method for preparing a high specific capacitance supercapacitor electrode based on a carbon material, comprising:
[0008] Step 1: mixing the carbon material with sodium alginate or carboxymethyl cellulose aqueous solution to obtain a slurry;
[0009] Step 2: coating the slurry onto a substrate to form a slurry film, immersing the slurry film and the substrate into a crosslinking agent for crosslinking, and then separating the hydrogel film from the substrate;
[0010] Step 3: The hydrogel film is washed with distilled water to remove residual cross-linking agent, and then immersed in an electrolyte for electrochemical treatment to obtain a high specific capacitance supercapacitor electrode.
[0011] In some embodiments, in step 1, the carbon material is selected from activated carbon, graphene, carbon black, carbon nanotubes or a combination thereof.
[0012] In some embodiments, in step 1, the feed ratio of the carbon material to sodium alginate or carboxymethyl cellulose is 2% to 20wt%, preferably 2% to 10wt%.
[0013] In some embodiments, in step 2, a blade coater is used to coat the slurry onto a substrate, which may be a glass plate. Preferably, the coating thickness is 200 to 1000 μm, preferably 400 to 600 μm. When the thickness is less than 200 μm, it will be difficult to separate the hydrogel film from the substrate; when the thickness is greater than 1000 μm, the film thickness will be uneven.
[0014] In some embodiments, in step 2, the cross-linking agent is a calcium chloride or aluminum chloride solution, and the concentration of the calcium chloride or aluminum chloride solution is 0.01 to 1 mol / L.
[0015] In some embodiments, in step 3, the electrolyte is selected from H2SO4, Li2SO4, ZnSO4, CaCl2 and Al2(SO4)3 electrolytes, preferably 3M H2SO4, 0.5M Li2SO4, 1M ZnSO4, 1M CaCl2 and 0.5MAl2(SO4)3 electrolytes.
[0016] In some embodiments, in step 3, the electrochemical treatment is achieved by performing CV cycles for 20-200 cycles at a scan rate of 5-50 mV / s.
[0017] In some embodiments, in step 3, the oxidation potential of the electrochemical treatment is 0.5-1.0 V (relative to Hg / Hg2SO4), preferably 0.5-0.7 V. When the oxidation potential is less than 0.5 V, the electrochemical stability window and capacitance improvement of the electrode are limited; when the oxidation potential is greater than 1.0 V, the electrode will be over-oxidized and the performance will deteriorate.
[0018] In a second aspect, the present invention provides a high specific capacitance supercapacitor electrode based on carbon materials obtained by the above preparation method.
[0019] In some embodiments, the supercapacitor electrode has an electrochemical stable potential window of up to 1.3V.
[0020] In some embodiments, the mass specific capacitance of the supercapacitor electrode is increased to 395 F / g.
[0021] In some embodiments, the supercapacitor electrode exhibits 99% capacitance retention after 20,000 cycles.
[0022] Technical Effects
[0023] The high specific capacitance supercapacitor electrode prepared by the present invention is made of a high ion conductive polymer hydrogel as a binder. Compared with the hydrogel formed by graphene self-crosslinking, the polymer hydrogel is simple to prepare and meets the conditions for large-scale preparation. As a binder, it can easily form a hydrogel electrode based on various active materials; and the polymer hydrogel has high ionic conductivity. When it is used as a binder, ions can penetrate the covering layer to reach all active sites, avoiding the "dead capacitance" caused by the blocking effect of the ion insulating binder, thereby releasing the intrinsic capacitance of the carbon material, and achieving an increase in capacitance of about 40%. In addition, oxygen-containing functional groups can be introduced on the electrochemically active surface of the carbon material through controllable electrochemical oxidation, which not only improves the oxidation resistance of the carbon material but also widens its electrochemical stable potential window by 30%, so that the electrochemical stable potential window of activated carbon, graphene, and carbon nanotube electrodes is widened to 1.3V, and pseudocapacitance is also introduced, so that the specific capacitance of the carbon material is further increased by about 45% (total increase exceeds 100%) on the basis of the previous step, and has high cycle stability.
[0024] By adjusting the potential of electrochemical oxidation, the degree of oxidation of the carbon material can be adjusted. The appropriate degree of oxidation can avoid damage to the conductive carbon skeleton and prevent the collapse of the porous structure. Controlling the oxidation potential at 0.5-0.7V can simultaneously achieve high specific capacitance, high rate performance and high cycle stability. The electrochemical stability window, specific capacitance and rate performance are taken into account. The electrode can be used as the positive and negative electrodes of symmetric supercapacitors. Because of its high oxidation resistance, it is also suitable as the positive electrode of asymmetric supercapacitors. The preparation method of the high specific capacitance supercapacitor electrode is simple, can be prepared on a large scale, and is flexible and robust.
[0025] The present invention can expand the electrochemical stable potential window by 30% and increase the specific capacitance by about 100% by using the existing commercially applied carbon materials and electrolytes. The preparation method is simple and compatible with the existing commercial production line, and can achieve large-scale preparation. The method provides an electrode for high energy density carbon-based supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A schematic diagram of ion transport in electrodes based on ion insulating binders and polymer hydrogel binders is shown. Figure 1 a is an electrode based on an ion-insulating binder, Figure 1 b is an electrode based on a polymer hydrogel binder;
[0027] Figure 2 shows the preparation and characterization of activated carbon / sodium alginate hydrogel electrodes, Figure 2 a is the preparation process of activated carbon / sodium alginate hydrogel electrode, Figure 2 b is the obtained flexible activated carbon / sodium alginate hydrogel electrode. Figure 2 c and 2d are SEM images of the surface direction of activated carbon / sodium alginate electrode. Figure 2 e and 2f are SEM images of the activated carbon / sodium alginate electrode in the cross-sectional direction;
[0028] Figure 3 The capacitance performance of activated carbon / sodium alginate hydrogel electrode and activated carbon / polyvinylidene fluoride electrode in a series of electrolytes is compared. Figure 3 a is the CV curve in 3M H2SO4, Figure 3 b is the CV curve in 0.5M Li2SO4, Figure 3 c is the CV curve in 1M ZnSO4, Figure 3 d is the CV curve in 1M CaCl2, Figure 3 e is the CV curve in 0.5MAl2(SO4)3, Figure 3 f is the gravimetric specific capacitance at a scan rate of 10 mV / s;
[0029] Figure 4 The electrochemical oxidation of activated carbon electrodes and its effect on the capacitive performance in 3M H2SO4 are shown. Figure 4 a is the CV curve of the activated carbon electrode from -0.7V to +1.2V (relative to Hg / Hg2SO4), Figure 4 b is the process of oxidizing the electrode at an oxidation potential of +0.6V. Figure 4 c is the CV curve of electrodes with different oxidation potentials. Figure 4 d is the electrochemical stability window and weight specific capacitance of electrodes at different oxidation potentials;
[0030] Figure 5 Characterization of the activated carbon electrode for electrochemical oxidation is shown, Figure 5 a is the atomic ratio of C and O at different oxidation potential electrodes, Figure 5 b is the Raman spectra of electrodes with different oxidation potentials, Figure 5 c is the infrared spectra of electrodes with different oxidation potentials, Figure 5 df is the X-ray photoelectron spectrum (C1s peak) of electrodes with different oxidation potentials;
[0031] Figure 6 The electrochemical performance of activated carbon electrodes at different oxidation potentials is shown. Figure 6 a is the ion storage kinetics of electrodes with different oxidation potentials, Figure 6 b is the rate performance of electrodes with different oxidation potentials based on weight specific capacitance, Figure 6 c is the rate performance of electrodes with different oxidation potentials based on volumetric capacitance, Figure 6 d shows the cycling stability of the electrode at an oxidation potential of +0.6 V;
[0032] Figure 7 The electrochemical properties of other electrochemically oxidized carbon materials are shown. Figure 7 a is the CV curve of the reduced graphene oxide (rGO) electrode before and after oxidation, Figure 7 b is the CV curve of the electrochemically exfoliated graphene (EG) electrode before and after oxidation. Figure 7 c is the CV curves of the multi-walled carbon nanotube (MWCNT) electrode before and after oxidation. DETAILED DESCRIPTION
[0033] The following describes the preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0034] Example 1
[0035] This example is a preparation example of high specific capacitance activated carbon / sodium alginate electrode. The specific steps are as follows:
[0036] Prepare a 10 mg / mL sodium alginate (SA) aqueous solution for later use. Figure 2 As shown in a, activated carbon (AC), carbon black (CB, content fixed at 10.0 wt%) and sodium alginate (SA) were mixed in water with stirring for 12 h to obtain a uniform AC / SA slurry;
[0037] The slurry is applied to the glass plate using an adjustable blade coater to form a uniform slurry film;
[0038] Then the slurry film together with the glass plate was immersed in a 1M CaCl2 aqueous solution for cross-linking. After 3 minutes, the AC / SA hydrogel film could be peeled off the glass plate.
[0039] Comparative Example 1
[0040] The electrodes were prepared using commercially available ion-insulating binders. The specific steps are as follows:
[0041] AC, CB (content fixed at 10 wt%) and polyvinylidene fluoride (PVDF) were mixed in NMP (N-methylpyrrolidone) solution with stirring for 12 h to obtain a uniform AC / PVDF slurry.
[0042] The slurry was coated on a glass plate using an adjustable doctor blade applicator and then dried at 60 °C for 12 h. After drying, the AC / PVDF electrode could be peeled off the glass plate.
[0043] The electrode surface loading can be controlled by adjusting the coating thickness of the coater.
[0044] Figure 2 b shows a photograph of an AC / SA electrode (5.0%-SA) with an SA content of 5.0 wt %. It can be seen that it has good flexibility and can be easily wound on a glass rod with a diameter of 6 mm.
[0045] Figure 2 cf shows the SEM images of the cross section and surface of the 5.0%-SA electrode. The results show that the SA region is composed of a network of SA lines and gaps. Figure 1 As shown in Figure 2, in the hydrogel state, these hydrophilic voids are filled with free water, allowing rapid ion transport, which allows ions to penetrate the SA cover layer to reach all electrochemically active surfaces, releasing the "dead capacitance" of the AC. The surface loading of the electrode was controlled by adjusting the coating thickness of the coater. The resulting AC / SA hydrogel electrode was washed 5 times with distilled water to remove residual Ca 2+ , and then immersed in the electrolyte for 2 hours for subsequent electrochemical treatment.
[0046] like Figure 3As shown, the capacitive performance of the 5.0%-SA electrode in various electrolytes was evaluated using a three-electrode architecture, and its mass specific capacitance was significantly improved. In 3M H2SO4, the mass specific capacitance of 5.0%-SA at 10mV / s was 267F / g, which was 39% higher than that of the activated carbon electrode PVDF electrode (5.0%-PVDF) using 5.0wt% polyvinylidene fluoride (PVDF) as a binder. It increased by 31%, 33%, 36% and 34% in 0.5M Li2SO4, 1M ZnSO4, 1M CaCl2 and 0.5MAl2(SO4)3, respectively. It can be seen that the ion conductive binder 5.0%-SA of the present invention can improve the capacitance of carbon materials in various electrolytes.
[0047] Electrochemical partial oxidation of the activated carbon electrode was achieved by 50 CV cycles at a scan rate of 20 mV / s in 3 M H2SO4 electrolyte (e.g. Figure 4 a, b). CV scans were performed at a fixed minimum potential (-0.7 V vs. Hg / Hg2SO4) and different maximum oxidation potentials (+0.5 V to +0.8 V vs. Hg / Hg2SO4). After oxidation at a potential of +0.7 V, the electrochemical stable potential window of the electrode increased from 1.0 V to 1.3 V, and its mass specific capacitance also increased from 267 F / g to 395 F / g ( Figure 4 c,d).
[0048] like Figure 5 As shown in the figure, through X-ray photoelectron spectroscopy, Raman spectroscopy, and infrared spectroscopy, it is known that the above changes are caused by the introduction of oxygen-containing functional groups into the activated carbon during the oxidation process. The oxygen-containing functional groups not only improve the antioxidant properties of the activated carbon, but also introduce pseudocapacitance with high specific capacitance.
[0049] like Figure 6 As shown, because the degree of oxidation is controlled within a reasonable range, the electrode with an oxidation potential ≤ 0.7 V also exhibits excellent rate performance and still shows a capacitance retention rate of 99% after 20,000 cycles.
[0050] Example 2
[0051] This example is a preparation example of a graphene / sodium alginate electrode with high specific capacitance reduction. The specific steps are as follows:
[0052] Prepare a sodium alginate (SA) aqueous solution with a concentration of 10 mg / mL for use. Mix graphene (including reduced graphene oxide and electrochemically exfoliated graphene), carbon black (CB, content fixed at 10.0 wt%) and sodium alginate (SA) in water and stir for 12 hours to obtain a uniform graphene / SA slurry; use an adjustable blade coater to apply the slurry to a glass plate to form a uniform slurry film; then immerse the slurry film together with the glass plate in a 1M CaCl2 aqueous solution for cross-linking. After 3 minutes, the AC / SA hydrogel film can be peeled off the glass plate. It has good flexibility and can be easily wound on a glass rod with a diameter of 6 mm. The obtained graphene / SA hydrogel electrode is washed 5 times with distilled water to remove residual Ca 2+ , and then immersed in the electrolyte for 2 hours for subsequent electrochemical treatment.
[0053] Electrochemical partial oxidation of the graphene electrode was achieved by 50 CV cycles at a scan rate of 20 mV / s in 3 M H2SO4 electrolyte. CV scans were performed with a fixed minimum potential (-0.7 V vs. Hg / Hg2SO4) and different maximum oxidation potentials (+0.5 V to +0.8 V vs. Hg / Hg2SO4).
[0054] like Figure 7 As shown in a and b, after oxidation at a potential of +0.7 V, the electrochemical stable potential window of the electrode increases from 1.0 V to 1.3 V, and its mass specific capacitance also increases significantly.
[0055] Example 3
[0056] This example is a preparation example of activated carbon / sodium carboxymethyl cellulose electrode with high specific capacitance reduction. The specific steps are as follows:
[0057] Prepare a 10 mg / mL sodium carboxymethyl cellulose (CMC) aqueous solution for use. Mix activated carbon (AC), carbon black (CB, fixed at 10.0 wt%) and CMC aqueous solution for 12 hours to obtain a uniform AC / CMC slurry; use an adjustable blade coater to apply the slurry to a glass plate to form a uniform slurry film; then immerse the slurry film and the glass plate in a 1M AlCl3 aqueous solution for cross-linking. After 3 minutes, the AC / SA hydrogel film can be peeled off the glass plate. It has good flexibility and can be easily rolled on a glass rod with a diameter of 6 mm.
[0058] Electrochemical partial oxidation of the activated carbon electrode was achieved by 50 CV cycles at a scan rate of 20 mV / s in 3 M H2SO4 electrolyte (e.g. Figure 4CV scans were performed with a fixed minimum potential (-0.7 V vs. Hg / Hg2SO4) and different maximum oxidation potentials (+0.5 V to +0.8 V vs. Hg / Hg2SO4).
[0059] Example 4
[0060] This example is a preparation example of a high specific capacitance multi-walled carbon nanotube / sodium alginate electrode. The specific steps are as follows:
[0061] Prepare a 10 mg / mL sodium alginate (SA) aqueous solution for later use. Mix the multi-walled carbon nanotubes (MWCNT) and sodium alginate (SA) aqueous solution with stirring for 12 hours to obtain a uniform graphene / SA slurry; use an adjustable blade coater to apply the slurry to a glass plate to form a uniform slurry film; then immerse the slurry film and the glass plate in a 1M CaCl2 aqueous solution for cross-linking. After 3 minutes, the MWCNT / SA hydrogel film can be peeled off the glass plate. It has good flexibility and can be easily wound on a glass rod with a diameter of 6 mm. The obtained MWCNT / SA hydrogel electrode is washed 5 times with distilled water to remove residual Ca 2+ , and then immersed in the electrolyte for 2 hours for subsequent electrochemical treatment.
[0062] Electrochemical partial oxidation of the MWCNT electrodes was achieved by 50 CV cycles at a scan rate of 20 mV / s in 3 M H2SO4 electrolyte. CV scans were performed with a fixed minimum potential (-0.7 V vs. Hg / Hg2SO4) and different maximum oxidation potentials (+0.5 V to +0.8 V vs. Hg / Hg2SO4).
[0063] like Figure 7 As shown in c, after oxidation at a potential of +0.7 V, the electrochemical stable potential window of the electrode increases from 1.0 V to 1.3 V, and its mass specific capacitance also increases significantly.
[0064] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a high specific capacitance supercapacitor electrode based on carbon material, comprising: Step 1: mixing the carbon material with sodium alginate or carboxymethyl cellulose aqueous solution to obtain a slurry; Step 2: coating the slurry onto a substrate to form a slurry film, immersing the slurry film and the substrate into a crosslinking agent for crosslinking, and then separating the hydrogel film from the substrate; Step 3: The hydrogel film is washed with distilled water to remove residual cross-linking agent, and then immersed in an electrolyte for electrochemical treatment to obtain a high specific capacitance supercapacitor electrode.
2. The preparation method according to claim 1, wherein In step 1, the carbon material is selected from activated carbon, graphene, carbon black, carbon nanotubes or a combination thereof.
3. The preparation method according to claim 1, wherein In step 1, the feed ratio of the carbon material to sodium alginate or carboxymethyl cellulose is 2% to 20wt%.
4. The preparation method according to claim 1, wherein In step 2, the coating thickness is 200 to 1000 μm.
5. The preparation method according to claim 1, wherein In step 2, the cross-linking agent is a calcium chloride or aluminum chloride solution, and the concentration of the calcium chloride or aluminum chloride solution is 0.01 to 1 mol / L.
6. The preparation method according to claim 1, wherein In step 3, the electrolyte is selected from H2SO4, Li2SO4, ZnSO4, CaCl2 and Al2(SO4)3 electrolytes.
7. The preparation method according to claim 1, wherein In step 3, the electrochemical treatment is achieved by performing CV cycles for 20-200 cycles at a scan rate of 5-50 mV / s.
8. The preparation method according to claim 1, wherein In step 3, the oxidation potential of the electrochemical treatment is 0.5-1.0V.
9. A high specific capacitance supercapacitor electrode based on carbon material obtained by the preparation method according to any one of claims 1 to 8.
10. The high specific capacitance supercapacitor electrode based on carbon material according to claim 9, which satisfies at least one of the following conditions: (1) The electrochemical stable potential window of the supercapacitor electrode is 1.3V; (2) The mass specific capacitance of the supercapacitor electrode is 395 F / g; (3) The supercapacitor electrode has a capacitance retention rate of 99% after 20,000 cycles.
Citation Information
Patent Citations
Graphene electrode plate and preparation method thereof
CN103839683A
Super capacitor electrode and preparation method thereof
CN105047432A
Carbon nanotube paper used in chemical power source electrode materials and activation method and application thereof
CN106158063A
Method for preparing all-alga solid-state supercapacitor and product thereof
CN107104000A
Preparation method of porous hydrogel membrane electrode
CN111146019A